Trends in cannabis use and attitudes toward legalization and use among Australians from 2001–2016: an age‐period‐cohort analysis. (7th October 2020) - Kaur, Navdep; Keyes, Katherine M.; Hamilton, Ava D.; Chapman, Cath; Livingston, Michael; Slade, Tim; Swift, Wendy
Abstract: Background and Aims: Changes in cannabis legalization and availability in Australia necessitate monitoring use and attitudes. We estimated age–period–cohort effects of past‐year cannabis use and attitudes toward criminalization and legalization. Design: Analysis of six waves of the Australian National Drug Strategy Household Survey (NDSHS) every 3 years (2001–2016). Setting and participants: The study was nationally representative of Australian households using multistage random sampling, totaling 145 168 respondents 18–79 years old. Data were collected using telephone, face‐to‐face, and drop‐and‐collect. Sample sizes per analysis varied based on data availability ( 107 000–127 000 per model). Measurements: Six waves of data for past‐year cannabis use (by sex and education), attitudes toward criminalization and legalization. Findings: Past‐year cannabis use decreased in young adults ages 18–35 from 2001–2016 (25.1%–18.6%) and increased in middle adults ages 36–55 (8.6%–10.1%) and older adults ages 56–79 (0.6%–3.0%). We observed a positive period effect and negative cohort effect for recent cohorts for past‐year use (e.g. 1955 cohort had 1.41 (95% CI: [1.11, 1.70]) increased log odds vs. 1998 cohort had −2.86 (95% CI: [−3.17, −2.55]) increased log odds) compared with the mean across years. Results were consistent by sex and varied by education. We observed a negative period effect for criminalization favorability (0.14 (95% CI: [0.003, 0.28]) increased log odds in 2001 vs. ‐0.31 (95% CI: [−0.45, −0.17]) increased log odds in 2016) and positive cohort effect for recent cohorts. Last, we observed a positive period effect for legalization support (−0.03 (95% CI: [−0.20, 0.14]) increased log odds in 2001 vs. 0.38 (95% CI: [0.22, 0.55]) increased log odds in 2016) and negative cohort effect for recent cohorts. Conclusion: Cannabis use appears to be increasing in Australia among adults over 35, while decreasing among adolescents and young adults. Legalization support also appears to have been increasing since 2007, signaling discordance between use and attitudes among adolescents and young adults, and potentially predicting increases in use over time.